A new dynamic modeling framework for credit risk assessment. (1st March 2016) - Sousa, Maria Rocha; Gama, João; Brandão, Elísio
Highlights: New approach to deal with changing environment in credit scoring modeling. Forecasting accuracy may significantly change on the presence of drifts in the context. New incoming data improve the knowledge about the new context. In stable conditions, old information may remain meaningful for predicting default. Abstract: We propose a new dynamic modeling framework for credit risk assessment that extends the prevailing credit scoring models built upon historical data static settings. The driving idea mimics the principle of films, by composing the model with a sequence of snapshots, rather than a single photograph. In doing so, the dynamic modeling consists of sequential learning from the new incoming data. A key contribution is provided by the insight that different amounts of memory can be explored concurrently. Memory refers to the amount of historic data being used for estimation. This is important in the credit risk area, which often seems to undergo shocks. During a shock, limited memory is important. Other times, a larger memory has merit. An application to a real-world financial dataset of credit cards from a financial institution in Brazil illustrates our methodology, which is able to consistently outperform the static modeling schema.